Understanding Speaking Difficulties Facing First Year Students of English at the Faculty of Education, Misurata University - Ben Nasr, Mohammed Ahmed (المجلة العلمية لكلية التربية, 2025)
The study investigates the main challenges faced by university students in Libya when speaking English and suggests ways to enhance their speaking skill in an English as a Foreign Language (EFL) environment. The research involved a questionnaire distributed among 20 first and second semester students from the English Department, Faculty of Education, Misurata University. It revealed that students encounter difficulties mainly in pronunciation, grammar, and vocabulary. The analysis of the questionnaire results showed varying degrees of confidence in speaking skills, with a significant percentage of students indicating struggles with grammar and vocabulary recall. The findings highlight that despite years of English education, students still face challenges in making effective communication, suggesting a gap between theoretical knowledge and practical applications. The study emphasizes the importance of practical speaking activities, exposure to authentic English materials, and the need for more interactive learning environments to improve students’ speaking abilities. The study concludes with recommendations for enhancing speaking skills through increased activities, vocabulary learning, and native English teacher involvement